Enriching Students’ Vocabulary Through The Application Of Total Physical Response (TPR) Method - Farisatma Farisatma (Journal on Education, 2023)
The aims of this study were to find out the extent to which TPR method contribute to students mastery of vocabulary. The research employed quantitative method with quasi-experimental design, control, and experimental group involved in pre-test and post-test. The research was carried out at SDN 1 Bonebone Baubau. Forty two students were purposively selected for samples divided in to two groups. Twenty one students were assigned for each group. Pre and posttest on vocabulary were presented on experimental and control group. Data were analyzed with statistical analysis and the use of independent t-sample and frequency test. The result indicated that TPR method contributed to the students’ vocabulary mastery. It was confirmed that the experimental group had better performance than control group. The analysis of posttest using independent sample t-test showed the probability value was 0.026 and it was less than 0.05 (0.026 ≤ 0.05). there were significant differences of posttest result between the experimental and control group.